TO STRUGGLE FOR HUMAN AND ECOLOGICAL LIBERATION: TOWARDS AN ECOLOGICAL THEOLOGY OF LIBERATION IN THE PHILIPPINE CONTEXT - Raluto, Reynaldo D (Asian Horizons, 2013)
This dissertation offers a theological reflection on the praxis of human and ecological struggle against oppressive relationships that produce global/local (“glocal”) poverty and the ecological crisis. It critically appropriates the framework of the emerging ecological theology of liberation, which embraces the broader notion of the preferential option for the poor — including the socio-economically poor, the socio-culturally oppressed (the indigenous peoples and women), and the victims of ecological exploitation (the natural world). Following this framework, my theological approach consists of three stages. First, I entered the “world” of the poor Filipinos whose direct and immediate experiences with oppressive relationships served as raw materials for my scientific analysis and theological reflection. Second, I used the analytical mediation of the social and ecological sciences to unmask the ideologies behind these oppressive relationships. In light of the hermeneutic mediation of Christian faith, I recognized these oppressive relationships as counter-signs of the coming of God’s Kingdom, which is the total liberation and salvation of the whole creation. And third, I used this inclusive regnocentric perspective on liberation to propose some transformative actions that appropriate the ethical imperatives of ecological praxis.